Diabetes Mellitus Patients' Experiences in Managing Diet during the COVID-19 Pandemic - Siti Ainul Kholipah; Nur Ela; Abi Surya Wijaya (Al Makki Publisher, 2025)
The COVID-19 pandemic has brought significant changes in people's lives, especially for patients with chronic diseases such as Diabetes Mellitus (DM). Consistent diet management is an important component of DM control, but the pandemic situation presents new challenges. This study aims to explore the experiences of DM patients in managing their diet during the COVID-19 pandemic. The research uses a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, questionnaires, and observations of seven purposively selected type 2 DM patients. The results of the study showed that the majority of patients had difficulty maintaining a regular diet due to limited access to healthy food, psychological pressure, and changes in daily routines. Family support helps maintain dietary discipline, while nutritional counseling services have been very limited during the pandemic. The average score of the questionnaire showed low consistency in the consumption of vegetables and fruits, as well as the low frequency of nutritional consultations. Observations of the home environment also show the dominance of instant food and a lack of healthy meal planning. In conclusion, the pandemic exacerbated the dietary management challenges in DM patients. Community-based interventions, sustainable nutrition education, and family involvement are needed to support effective management of DM in times of crisis.